Elements of language and assimilation of Malay language in Baba and Nyonya community in Malaysia - Vijayaletchumy, Subramaniam; Wan Mohammad, Wan Muna Ruzanna (Canadian Center of Science and Education, 2010)
The purpose of this research is to identify the elements of language and to study the strength of the assimilation of the Malay language used by the Baba and Nyonya in Malacca. This research is focusing on the aspects of language that cover the usage level of the language, pronunciation, spelling, vocabulary and others. This research uses library research, survey, observation and interview. Questionnaires have been distributed to all respondents as the procedure to conduct the research. The level of the assimilation of the Malay language in Baba and Nyonya has been analyzed from the angles of frequency, mean and standard deviation and are explained rationally.